EVALUASI PENYIMPANAN OBAT LASA DI INSTALASI FARMASI RUMAH SAKIT STELLA MARIS MAKASSAR - Suhartini Suhartini (Akademi Farmasi Yamasi Makassar, 2022)
Storage is a security activity to avoid drugs from physical and chemical damage so as to ensure the quality of drugs is guaranteed, this study aims to find out how to store LASA drugs at the Pharmacy Installation of Stella Maris Hospital Makassar. The type of research conducted is descriptive through data collection by observation, the population used in this study is all drugs contained in the pharmacy installation of Stella Maris Hospital Makassar. Data collection was done by direct observation with a checklist system using an observation table, based on the LASA drug storage mechanism.The results showed that of the ten (10) requirements for the LASA drug storage system, 8 requirements were met and 2 requirements suitable so that a conformity value of 80% was obtained, which means that it is classified as good in the drug storage process.